STUDYING THEORETICAL ANALYSIS OF DRIVING FORCES OF COTTON PIECES ENTERING THE SEPARATOR WORKING CHAMBER (Ta'limning zamonaviy transformatsiyasi, 2024)
In this article, the impact of cotton particles entering the separator working chamber together with the air flow on the elastic plank located at a certain distance from the entrance path and forming an angle with the vertical direction, and the impact process between the cotton particles and the elastic plank is theoretically analyzed. Graphs of changes in the movement of a piece of cotton from the surface of the entrance to the separator to the elastic plate. Methods of conducting research and tests. A theoretical study of the movement of cotton pieces to an elastic plank. Mathematical model developed graphs are built.